ENVIRONMENTAL AND HYGIENIC ASPECTS OF THE FORMATION OF HIGH PROFESSIONAL CAPACITY OF MODERN PUPILS AND STUDENTS - Serheta , Ihor (Collection of scientific papers «ΛΌГOΣ», 2023)
At the current stage of the development of society, one of the most important tasks of preventive medicine should be considered the preservation and strengthening of health, increasing the level of social and professional capacity of children, adolescents and young people [1, 2, 3].